2006
DOI: 10.1158/1078-0432.ccr-06-0501
|View full text |Cite
|
Sign up to set email alerts
|

Validity of Messenger RNA Expression Analyses of Human Saliva

Abstract: Purpose: The origins of expression microarray and reverse transcription-PCR (RT-PCR) signals in human saliva were evaluated. Experimental Design: The ''RNA'' extracts from human saliva samples were treated with vehicle, DNase, or RNase. Two-step amplification and hybridization to Affymetrix 133A cDNA microarrays were then done. Confirmatory RT-PCR experiments used conventionally designed PCR primer pairs for the reference housekeeper transcripts encoding 36B4, h-actin, and glyceraldehyde-3-phosphate dehydrogen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
31
1
1

Year Published

2007
2007
2021
2021

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 48 publications
(34 citation statements)
references
References 15 publications
1
31
1
1
Order By: Relevance
“…The capability to study partially fragmented and degraded RNA from nonideal samples is imperative in (24 ) has been well addressed in various studies in our laboratory (9,18,25,26 ) as well as by other independent investigators (27 ); however, these compromised RNAs impose great challenges to the prevailing approaches to their characterization. Transcript fragments often lack the poly(A) tail, and the fragmentation pattern is likely to be random (18 ).…”
Section: Discussionmentioning
confidence: 99%
“…The capability to study partially fragmented and degraded RNA from nonideal samples is imperative in (24 ) has been well addressed in various studies in our laboratory (9,18,25,26 ) as well as by other independent investigators (27 ); however, these compromised RNAs impose great challenges to the prevailing approaches to their characterization. Transcript fragments often lack the poly(A) tail, and the fragmentation pattern is likely to be random (18 ).…”
Section: Discussionmentioning
confidence: 99%
“…It has recently been suggested (22 ) that expression microarray and quantitative PCR analysis of saliva specimens might be detecting genomic DNA, rather than mRNA as claimed (23 ). This assertion was based on observations that "no-RT" (i.e., no reverse transcriptase included in the cDNA reaction) and "ϩRT" (reverse transcriptase included) reactions yielded similar amounts of PCR product, that microarray signals were unaffected by RNase treatment, and the absence of RT-PCR products after DNase treatment.…”
Section: Discussionmentioning
confidence: 99%
“…We have observed that similar to plasma the endogenous cell-free mRNA in saliva is protected from immediate degradation [13,14]. Meanwhile, the salivary mRNA finding has been challenged by others unable to detect mRNA in saliva supernatant and also not in whole saliva [15]. However, while the method used for RNA detection is mRNA specific, it has a reduced sensitivity and stands in direct conflict with the fragmented nature of salivary mRNA.…”
Section: Salivary Transcriptomementioning
confidence: 95%